Development of Poketun Application (Augmented Reality-Based Pocket Book of Pantun) to Improve Children’s Literacy Skills and Literary Appreciation - Rahman, Ahmad Syaeful; Bahtiar, Ahmad (DISASTRA: PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2026)
This study aims to develop Poketun (Pocket Book Pantun Based on Augmented Reality) as an interactive digital medium to enhance elementary school students’ reading literacy and literary appreciation. The research adopted a research and development (R&D) design with a qualitative approach, based on the 4D development model (Define, Design, Develop, Disseminate). Data were collected through observation, interviews, documentation, and expert validation, and were subsequently analyzed descriptively. The results revealed that students’ initial reading literacy and pantun appreciation were still low; most students merely memorized pantun without understanding their aesthetic and moral values. The Poketun application was then designed with thematic pantun content, AR visualization, audiovisual features, and interactive tools that support both reading and composing pantun. Expert validation indicated that the application was feasible to use, with suggestions for improvement such as simplifying navigation, adding more diverse pantun, and providing offline access. Classroom implementation showed positive responses: students were more enthusiastic, motivated to read, and better able to grasp the meaning of pantun. Teachers also reported that the application enriched learning variation and reduced students’ boredom. The novelty of this study lies in integrating AR with literary learning, in contrast to previous studies that mostly focused on science or mathematics. Theoretically, the study expands the discourse on reading literacy and children’s literary appreciation in digital contexts, while practically, it offers innovative learning media and contributes to preserving local cultural heritage.